Opening Minds in Canada: Background and Rationale. (January 2014) - Stuart, Heather; Chen, Shu-Ping; Christie, Romie; Dobson, Keith; Kirsh, Bonnie; Knaak, Stephanie; Koller, Michelle; Krupa, Terry; Lauria-Horner, Bianca; Luong, Dorothy; Modgill, Geeta; Patten, Scott B; et al.
Objective: To summarize the background and rationale of the approach taken by the Mental Health Commission of Canada's Opening Minds (OM) Anti-Stigma Initiative. Method: The approach taken by OM incorporates a grassroots, community development philosophy, has clearly defined target groups, uses contact-based education as the central organizing element across interventions, and has a strong evaluative component, so that best practices can be identified, replicated, and disseminated. Contact-based education occurs when people who have experienced a mental illness share their personal story of recovery and hope. Results: OM has acted as a catalyst to develop partnerships between community groups who are undertaking anti-stigma work and an interdisciplinary team of academic researchers in 5 universities who are evaluating the results of these programs. Conclusions: Building partnerships with existing community programs and promoting systematic evaluation using standardized approaches and instruments have contributed to our understanding of best practices in the field of anti-stigma programming.